Diagnostic Accuracy of Intra-Abdominal Pressure Measurement Method via Bladder in Predicting Renal Dysfunction after Kidney Transplantation - Mahtab Torkamani; Nahid Aghebati; Hamid Heidarian Miri; Mahmoud Tavakoli; Ahmad Farid Ejaz (Mashhad University of Medical Sciences, 2021)
Background: The patients undergoing kidney transplantation are exposed to Intra-Abdominal Pressure (IAP) elevation following a surgery.Aim: The present study aimed to evaluate the diagnostic accuracy of the IAP measurement method via bladder in the prediction of renal dysfunction after kidney transplantation.Method: This longitudinal study was conducted on 135 kidney transplant patients in two hospitals in Iran/Afghanistan from February 2019 to the end of October 2019. The patients' IAP was measured by nurses every 6 h up to 24 h after the surgery. The indices of renal dysfunction were utilized, including creatinine increase and urine reduction. Doppler ultrasound was used as a golden standard diagnostic test. Data were analyzed in STATA 14.Results: Out of 135 patients, an increase in IAP>10 mmHg was observed in 9.5% of cases. Urinary loss and creatinine decrease more than 25% of baseline indicated a significant correlation with IAP mean difference (P=0.001) (4-1). Therefore, IAP could predict renal dysfunction based on the reduction of urinary volume and a decrease in creatinine of more than 25% of baseline. Finally, a comparison between the diagnostic power of the IAP measurement method and Doppler ultrasound indicated 90% of sensitivity and 94% of negative predictive value in predicting renal dysfunction.Implications for Practice: As evidenced by the obtained results, the IAP measurement via bladder catheter might be a primary test to predict renal dysfunction before Doppler ultrasound; nonetheless, further research is required.